Differential inhibition of thrombin generation by vitamin K antagonists alone and associated with low-molecular-weight heparin - Gerotziafas, Grigoris T.; Dupont, Charlotte; Spyropoulos, Alex C.; Hatmi, Mohamed; Samama, Meyer M.; Kiskinis, Dimitris; Elalamy, Ismail (Thrombosis and Haemostasis, 2009)
Vitamin K antagonists (VKA) treatment starts with co-administration of low-molecular-weight heparin (LMWH). The anticoagulation induced by the two drugs is still not well determined. In the present study we used thrombin generation assay to evaluate the hypo-coagulation induced by treatment with VKA and by the combination of VKA with LMWH. Tissue factor triggered thrombin generation in platelet-poor plasma was assessed in samples from 15 healthy volunteers, 97 samples from patients treated with VKA and 41 samples from patients receiving enoxaparin and VKA. Patients were classified according to international normalised ratio (INR) level (<2, 2–3 and >3).In plasma samples from patients treated with VKA having INR 2–3 the inhibition of thrombin generation reached 50% compared to controls. In samples with INR>3 this inhibition was 80%. In samples from patients receiving both LMWH and VKA, thrombin generation was significantly decreased compared to the controls and VKA group. In samples with an INR 2–3 obtained from patients treated with LMWH and VKA, the inhibition of thrombin generation was similar to that observed in samples with an INR>3 obtained from VKA treated patients. Thrombin generation assay is sensitive to detect the global the anticoagulant effect produced by the association of LMWH and VKA. For equal INR dual anticoagulant treatment induces significantly more profound inhibition of thrombin generation compared to treatment with VKA alone. The clinical relevance of this observation merits to be studied in prospective studies in patients with defined indications of anticoagulant therapy.
Keywords: Oral anticoagulants; vitamin K antagonists; bridging treatment; LMWH; thrombin generation